Granulomatous Inflammation Masking Nodular Lymphocyte Predominant Hodgkin Lymphoma: A Diagnostic Pitfall - Sharma, Renu; Chauhan, Pooja; Kumari, Kavita (Annals of Pathology and Laboratory Medicine, 2025)
Extensive granulomatous inflammation in a lymph node is a significant diagnostic pitfall that can mask underlying malignancies, including Nodular Lymphocyte-Predominant Hodgkin lymphoma (NLPHL). Hodgkin lymphomas are lymphoid neoplasms with characteristic Reed-Sternberg cells (RS cells) and variants of RS cells in the mixed reactive background of neutrophils, eosinophils, plasma cells, and polymorphic lymphoid cell population. Granulomatous inflammation occasionally may accompany the polymorphic mixed reactive population but is sometimes so extensive that it masks the primary underlying pathology. This can lead to delayed and missed diagnosis. We report a rare case of Nodular Lymphocyte-Predominant Hodgkin lymphoma (NLPHL) masked by exuberant granulomatous lymphadenitis.